2009
DOI: 10.1093/jac/dkp445
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic Helicobacter pylori clarithromycin resistance and therapeutic outcome: benefits and limits

Abstract: This study showed that: (i) there is a relevant discordance between the two methods; and (ii) phenotypic clarithromycin resistance markedly reduces H. pylori eradication when it is linked to a specific point mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 31 publications
8
72
3
2
Order By: Relevance
“…However, some differences between phenotype and genotype profiles were observed; these were characterized by phenotypic susceptibility and genotypic resistance or vice versa, in contrast to other studies [22][23][24].…”
Section: Discussioncontrasting
confidence: 86%
“…However, some differences between phenotype and genotype profiles were observed; these were characterized by phenotypic susceptibility and genotypic resistance or vice versa, in contrast to other studies [22][23][24].…”
Section: Discussioncontrasting
confidence: 86%
“…Notably, the eradication rate showed the lowest value (30.7%) when the phenotypic bacterial resistance was genetically linked to the A2143G point mutation. The conclusion of this study was that there is a disagreement between the two methods; clarithromycin resistance markedly reduces H. pylori eradication only when it is linked to a specific point mutation [26] . On these grounds, it has been suggested that MIC values for clarithromycin resistance should be dropped to 0.5 in order to improve the efficacy of phenotypic detection [27] .…”
Section: Methods For Clarithromycin Resistance Detectionmentioning
confidence: 89%
“…In particular, point mutations at positions 2143 (A to G) and 2142 (A to G or C) are responsible for Ͼ90% of clarithromycin resistance cases (9). Moreover, the presence of the A2143G mutation is strongly associated with eradication therapy failure (10,11). A lower prevalence of the A2142G/C mutation has been reported (11), but these mutations are also commonly found in patients for whom clarithromycin-based treatment failed to eradicate the infection.…”
mentioning
confidence: 99%